Escrito en el lienzo: Ovidio y el Billete de Amor en La Enferma de Amor de Jan Steen, pintor holandés del Siglo de Oro = Written on the Canvas: Ovid and the Billet-Doux in The Lovesick Maiden by Jan Steen, Golden Age Dutch Painter - Díaz Gito, Manuel Antonio (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2020)
Se analiza la impronta de la poesía erótica de Ovidio sobre un tema favorito del pintor barroco de Leiden Jan Steen (1626-1679), La enferma de amor o La visita del médico, con especial atención a la presencia en el cuadro de un billete de amor con una máxima escrita de origen ovidiano sobre el tradicional concepto del amor como una enfermedad incurable:… amor non est medicabilis herbis (epist. 5.149). Abstract Analysis of the influence of Ovid’s erotic poetry on a favourite theme to the Leiden Baroque painter Jan Steen (1626-1679), The lovesick maiden or The doctor’s visit, especially focalised on the presence of a billet-doux with an Ovidian written refrain on the traditional concept of love as an incurable illness: … amor non est medicabilis herbis (epist. 5.149).